Mémoires de l’esclavage et redémocratisation à Rio de Janeiro (1978-1988) - Thaís Tanure (Nuevo mundo - Mundos Nuevos)
This article focuses on the development of various memories of slavery, in line with two political periods: the end of the Brazilian military dictatorship (1964-1985) and the democratization. The racial claims related to the legacy of slavery and the management of these demands by the dictatorial government are analyzed. In a second part, the construction of a monument to the quilombola leader Zumbi dos Palmares and the heritage designation of Pedra do Sal in Rio de Janeiro are examined. These memorial initiatives align with a new civic pact, formalized in 1988 by a new constitution of the country – a year that also marks the centenary of the abolition of slavery – and represent a pivotal moment when memory practices clash in the urban space.